The aesthetics of mythical violence in Hong Kong action films - Teo, Stephen (New Cinemas: Journal of Contemporary Film, 2011)
Hong Kong cinema is known throughout the world for its action cinema, including martial arts films and gangster pictures that portray violence as an integral part of their appeal. This article examines the nature of violence in contemporary Hong Kong cinema, borrowing concepts from Walter Benjamin's essay Critique of violence to define the violence in Hong Kong action films as mythical and aestheticized. The article analyses a body of films such as King Hu's classic A Touch of Zen (197071), John Woo's A Better Tomorrow (1987) and Johnnie To's Election (2004) to support its thesis. The mythical violence portrayed in these films, it is argued, constructs a critique of violence. Furthermore, the films set up a wider framework of discourse about violence itself as a method of questioning social institutions and norms affecting gender.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjguMy4xNTVfMQ